Determinant Factor of Transformational Leadership in the Age of Globalization - Rajamemang Rajamemang; Tahir Kasnawi; Anshari Anshari; Fakhri Kahar; Rusdi Maidin (Jurnal Ad'ministrare, 2019)
This study aims to determine the supporting and inhibiting factors of Transformational Leadership in the Age of Globalization. The research location was conducted at Bosowa University. The technique of collecting data uses observation, interviews, FGD. Data analysis techniques use the theories of Miles, Huberman and Saldana (2014). The results of the study show that the determinant factors in this study can be seen from two factors: university supporting factors and inhibiting factors. Supporting factors: it has been illustrated that the Chancellor as a leader has a network that has been developed both at the local, regional, national and international levels. Furthermore, it is supported by adequate learning process facilities. So as to be able to compete with other universities in Indonesia. The inhibiting factors are the availability of limited teaching staff.